2015
DOI: 10.1523/jneurosci.0012-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response and Cholesterol Biosynthesis Link Luman/CREB3 to Regenerative Axon Growth in Sensory Neurons

Abstract: We recently revealed that the axon endoplasmic reticulum resident transcription factor Luman/CREB3 (herein called Luman) serves as a unique retrograde injury signal in regulation of the intrinsic elongating form of sensory axon regeneration. Here, evidence supports that Luman contributes to axonal regeneration through regulation of the unfolded protein response (UPR) and cholesterol biosynthesis in adult rat sensory neurons. One day sciatic nerve crush injury triggered a robust increase in UPR-associated mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Further analysis comparing nerve injury-induced mRNAs to genes known to be upregulated in an ATF4-dependent manner after neuronal oxidative stress (Lange et al, 2008) revealed that the expression changes observed in this ISR-related gene set is greater than would be expected by chance in both axonal injury models (Figure 1c,d). Together these observations suggested the hypothesis that the acute neuronal stress response may include activation of PERK signaling in multiple settings, consistent with a report that nerve crush leads to PERK phosphorylation (Ying et al, 2015).
10.7554/eLife.20725.002Figure 1.Acute neuronal insults activate the integrated stress response (ISR).( a ) Schematic of sciatic nerve crush (SNC) and optic nerve crush (ONC).
…”
Section: Resultssupporting
confidence: 90%
“…Further analysis comparing nerve injury-induced mRNAs to genes known to be upregulated in an ATF4-dependent manner after neuronal oxidative stress (Lange et al, 2008) revealed that the expression changes observed in this ISR-related gene set is greater than would be expected by chance in both axonal injury models (Figure 1c,d). Together these observations suggested the hypothesis that the acute neuronal stress response may include activation of PERK signaling in multiple settings, consistent with a report that nerve crush leads to PERK phosphorylation (Ying et al, 2015).
10.7554/eLife.20725.002Figure 1.Acute neuronal insults activate the integrated stress response (ISR).( a ) Schematic of sciatic nerve crush (SNC) and optic nerve crush (ONC).
…”
Section: Resultssupporting
confidence: 90%
“…A potential area of interest will be to determine whether the endoplasmic reticulum stress pathway and the miRNA biogenesis pathway, which are known to regulate each other, do so in the context of axon regeneration 184,185 . This is possible given that the endoplasmic reticulum stress response promotes regeneration of sensory neurons 91,186 and survival of RGCs 187 .…”
Section: Role Of Micrornas In Injured Neuronsmentioning
confidence: 99%
“…However, this pathway may play a role in mammalian axon regeneration since retinal ganglion cells from Rtca mutant mice have a substantial increase in the number of regenerating axons (Song et al, 2015). Additionally, the UPR is activated by sciatic nerve crush in adult rat sensory neurons with enhanced expression of the core components CHOP and XBP1 (Ying et al, 2015). Finally, addition of tunicamycin, which induces the UPR, can rescue the decrease in axon regeneration seen in mutants of the ER-resident transcription factor Luman/Creb3 (Ying et al, 2015).…”
Section: Larval Laser Axotomy Modelsmentioning
confidence: 99%
“…Additionally, the UPR is activated by sciatic nerve crush in adult rat sensory neurons with enhanced expression of the core components CHOP and XBP1 (Ying et al, 2015). Finally, addition of tunicamycin, which induces the UPR, can rescue the decrease in axon regeneration seen in mutants of the ER-resident transcription factor Luman/Creb3 (Ying et al, 2015). Hence, the RNA ligase complex may promote axon regeneration by facilitating the capacity of the UPR to promote axonal regeneration.…”
Section: Larval Laser Axotomy Modelsmentioning
confidence: 99%